Pengaruh Profitabilitas, Likuiditas, dan Pertumbuhan Penjualan terhadap Kebijakan Hutang: Studi Empiris Perusahaan Properti Di BEI Tahun 2021-2024 - Christy Amelia Rotua Sibarani; Jumiadi (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The problem in this study is related to significant fluctuations in the level of debt utilization by property and real estate companies in Indonesia during the pandemic and post-pandemic periods. This study aims to examine the effect of profitability, liquidity, and sales growth on debt policy. This research employed a quantitative approach using secondary data obtained from the companies’ annual financial statements. The population consisted of property and real estate companies listed on the Indonesia Stock Exchange for the period 2021–2024. The sampling technique applied was purposive sampling, resulting in a total sample of 30 companies. The analytical methods used in this study were descriptive statistical analysis and panel data regression analysis, with the assistance of EViews 12 software. The results of this study show that profitability has no effect on debt policy, liquidity has a negative and significant effect on debt policy, and sales growth has no effect on debt policy. The findings also indicate that simultaneously, profitability, liquidity, and sales growth affect debt policy.